Interpretation on the pil test in Panama in the context of the Covid-19 effect of relaxation activities. - Romero-Ramos, Néstor; González Suárez, Arnoldo José; Romero-Ramos, Óscar (My University, 2020)
The pandemic decreed by WHO by the COVID-19 virus and the possibility of causing harm to the health and death of people, especially the elderly, it has led states to issue orders for confinement and suspension of activities such as education, to mitigate the spread of the virus. The purpose of this study is to interpret the PIL test and its relationship to relaxation in panamanian citizens in confinement. To this end, a survey was conducted in online form to 533 individuals (39±11 years) using the Purpose in Life (LIP) test and an ad-hoc questionnaire for know physical activity (AF), mental relaxation (MRI), hours of sleep, and concerns and satisfaction during confinement. A subgroup of participants conducted targeted MRI activities (n = 19) and the PIL score was compared with another group that did not perform MRI activities (n = 38). At most 73% of respondents performed 120 min of AF per week, indicating prevalence of physical inactivity. 90% perform up to 120 min of MRI per week. The overall mean of the PIL test was 114±16, indicating a strong life purpose, and there were no differences by sex, or by levels of physical activity, but for relaxation time and age. The scores of the PIL test were positively correlated with the age and time of MRI. On the other hand, the main concern of panamanians is the economy (50%) and health or getting sick by COVID-19 (37%) and what gives the greatest satisfaction is the family (40%) and sharing and spending time with the family (33%). The group that performed the suggested MRI activities obtained a significantly higher PIL test value (123±12) than the group that did not perform the MRI activities (108±17). In conclusion, despite the general stress caused by confinement, the group evaluated enjoys sharing with their loved ones. In general, home AF and MRI should be promoted for stress management during confinement.
Keywords: Ejercicio físico; Felicidad; Estrés; Epidemias; Coronavirus-Aspectos psicológicos; Psicometría; Coronavirus-Panamá; Confinement; Physical activity; Happiness; Stress